Finland's energy system for 2030 as envisaged by expert stakeholders. (December 2017) - Toivanen, Pasi; Lehtonen, Pinja; Aalto, Pami; Björkqvist, Tomas; Järventausta, Pertti; Kilpeläinen, Sarah; Kojo, Matti; Mylläri, Fanni
Abstract: To reach the 2030 decarbonization targets, EU Member States develop national strategies. We examine the views of key stakeholders in Finland to outline how those responsible for developing, steering and implementing the energy system assess the various solutions. The Finnish choices are of interest owing to the mixture of assets, constraints and path-dependencies shaping them. Our Q methodological analysis uncovers three main views: international competition and smart solutions; active consumers; national competitiveness and local solutions alongside a consensus upon which the implementation of Finland's own 2030 strategy can be built. The key stakeholders in Finland are ready for solutions comprehensively shaping the energy system, which can also influence several vested interests, existing business models and eventually break existing path-dependencies. Highlights: We study the views of key stakeholders of the 2030 energy system in Finland. View I stresses international competition and smart solutions. View II focuses on active consumers. View III combines national competitiveness and local solutions. The stakeholders also have a common ground on which to build a 2030 strategy.